How small circuits power big technology in the world of VSIL - V. Basil Hans (International Journal of VLSI Circuit Design & Technology, 2025)
Very Small Integration Level (VSIL) circuit technology represents an emerging class of ultra- compact, low-power electronic design methodologies that enable the creation of highly efficient and scalable systems. This article explores the fundamental principles behind VSIL circuits, including device miniaturization, optimized layout strategies, adaptive power management, and noise-resilient architectures. We also look into the methodical engineering of VSIL circuits to satisfy the ever-tougher performance, robustness, and long- term energy-efficiency demands of contemporary and developing application areas. These fields include distributed environmental sensing platforms, wearable health monitoring devices, implanted biomedical systems, next-generation IoT edge nodes, and small autonomous agents that can make decisions in real time. We demonstrate the special benefits that VSIL technology provides in settings where traditional integration paradigms are constrained by size, cost, or power limitations by examining various use scenarios. We examine how VSIL circuits are engineered to meet the stringent performance, reliability, and energy demands of modern applications—from wearables and biomedical implants to next- generation IoT edge devices. Recent advances in materials, fabrication processes, and design automation tools are highlighted, illustrating the rapid evolution of the VSIL design landscape. Finally, we discuss current challenges such as thermal constraints, variability at nanoscale dimensions, and integration complexity, while outlining future trends that position VSIL technology as a cornerstone of the next wave of compact intelligent systems.
Keywords: IoT and Embedded Systems; Low-power design; Miniaturized Circuits; Nanoscale Integration; VSIL Technology